THE EFFECT OF FASTING BLOOD GLUCOSE LEVELS ON LIPID PROFILES - Novendy Novendy; Silviana Tirtasari (Ebers Papyrus, 2025)
Metabolic diseases have become a common health problem faced by many people in Indonesia. Two important indicators for monitoring the onset of metabolic diseases are blood glucose and blood lipids. Blood glucose has a strong physiological relationship with lipid metabolism, including triglycerides, total cholesterol, LDL, and HDL. Excess blood glucose that is not utilized by the cells is converted into fatty acids through the process of lipogenesis in the liver, which are then stored as triglycerides, leading to elevated blood lipid levels that may contribute to the development of metabolic diseases. One private clinical laboratory in Tangerang City has received numerous test requests related to blood glucose and blood lipids. However, no analysis has been conducted to date, highlighting the need for a research study. This study employed a cross-sectional design and analyzed a total of 322 samples that met the inclusion criteria. The results showed a significant association between fasting blood glucose levels and triglyceride levels (p-value = 0.0001, PRR = 2.93), as well as HDL levels (p-value = 0.01, PRR = 1.469). However, no significant relationship was found between fasting blood glucose and total cholesterol (p-value = 0.209, PRR = 1.710) or LDL levels (p-value = 0.977, PRR = 0.993). These findings emphasize the importance of controlling blood glucose levels to prevent lipid metabolism disorders, even though not all lipid profile components showed a similar association.